Two new subfamilies in Lamiaceae - Li, Bo; Olmstead, Richard G. (Phytotaxa, 2017)
Two new subfamilies, Callicarpoideae Bo Li & R.G.Olmstead and Tectonoideae Bo Li & R.G.Olmstead, are established within the mint family. Their morphology, distribution, generic and species diversity, homotypic tribes, and phylogenetic position are noted.